Pemanfaatan Metode Penyuluhan Pertanian oleh Petani Cabai Merah - Yanuar Dwi Ramadhana; Sri Subekti (Jurnal KIRANA, 2021)
The contribution of extension and the use of innovation in agriculture, especially red chili, is needed by farmers to improve agricultural development. Agricultural extension to the red chili farming community in Tamansari Village, Wuluhan District, Jember Regency, East Java, to improve farmers' knowledge and skills regarding an innovation and help increase production. The application of extension methods to red chili farmers has different responses in accepting an innovation or technology. The purpose of this study was to find out how the use of extension methods through individual, group and mass methods in the innovation adoption process by red chili farmers. This research is qualitative by presenting a complete picture of the social condition of the phenomenon and analyzed by Miles and Hubberman. Determination of informants in this study was carried out using purposive sampling method, this study had 1 key informant namely the head of the farmer group and 10 supporting informants in this study which was carried out using the snowball sampling method, namely extension workers, formulators and farmers who were active in extension activities. The results showed that counseling was carried out using 3 methods, namely individual methods with home visits, land visits, informal contacts and inquiry. Group method with lecture, discussion, demonstration and field school techniques. Mass method with campaign technique, internet, radio and television. After counseling with 3 methods and each technique, farmers can accept and apply a technological innovation, namely: a) organic pesticides, b) the use of Plant Growth Promoting Rhyzobacteria (PGPR), c) tractors, d) diesel engines, e) charcoal husks, f) water pumping machines, g) demonstration plots of fertilizers and pesticides, h) superior seeds, i) partners with Bank Mandiri & BNI, j) cooperation with PT Dirga Guna Wibawa (DGW), PT Advanta and PT Arista, k) use of internet media. Keyword: Extension, Extension Methods, Red Chili, Adoption of Innovations, Farmer Groups